Clinical and psychological characteristics of patients with psoriasis reporting various frequencies of pruritus. (21st November 2013) - Janowski, Konrad; Steuden, Stanisława; Bogaczewicz, Jarosław
Abstract Background Pruritus is a common subjective symptom of psoriasis whose levels may be affected by a range of variables. The objective of this study was to evaluate the frequency of pruritus and its associations with clinical and psychological characteristics of psoriasis patients. Materials and methods One‐hundred and seventy‐four patients with psoriasis took part in the study, and they were assessed on clinical (psoriasis area and severity index [PASI], localization of lesions, pruritus severity, duration of the disease) and psychological (coping, personality, cognitive appraisal of the disease, quality of life) variables. ANOVA, Pearson's χ2‐tests, and correlational analyses were employed to analyze the data. Results The frequency of reported pruritus was found to be related to PASI (P < 0.000) and localization of skin lesions on visible body areas (P < 0.05). Patients reporting more frequent pruritus were significantly older (P < 0.05), had lower quality of life (P < 0.000), more frequently used coping strategies of resignation (P < 0.05) and self‐blame (P < 0.05), and tended to appraise their disease in terms of a threat (P < 0.05), obstacle/loss (P < 0.05), and harm (P < 0.01). No significant associations were found between pruritus and basic personality traits. After controlling for age, all these variables remained significantly correlated with pruritus, whereas after controlling for psoriasis severity, only age, quality of life, and a coping strategy of resignation still significantly correlated with pruritus frequency. Conclusions The findings emphasize the importance of pruritus in the majority of psoriasis patients and its significant association with compromised quality of life, older age, greater psoriasis severity, and a specific pattern of psychological responses to stress.